Designing an Academic Advising Information System: A Human-Centered Design Approach - Angelia Angelia; Johan Jimmy Carter Tambotoh (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
The digital transformation in higher education necessitates a reliable academic advising information system to enhance student support and academic decision-making. This study presents the design of an Academic Advising Information System using a Human-Centered Design (HCD) approach to address various challenges in academic advising, including ineffective communication, fragmented platforms, and inefficient documentation. By applying HCD principles, the system prioritizes usability, accessibility, and emotional considerations, ensuring an intuitive and supportive user experience for both students and academic advisors. This study follows an iterative development framework, integrating user insights through observations, interviews, and iterative improvements to refine system features such as advising history tracking and streamlined communication channels. The results indicate that the application of HCD effectively optimizes advising interactions, reduces administrative burdens, and enhances student engagement. This study contributes to the broader discourse on user-centered educational technology, emphasizing the importance of aligning digital solutions with user expectations. Future research should explore the scalability and adaptability of this system across various academic institutions to validate its broader applicability.